Responsive Adaptive Curriculum: Building Inclusive Education Oriented On Student Independence In Islamic Boarding School - Rofi'atul Munawaroh; Pateemoh Meedeng (Journal of Social Studies and Education, 2024)
This study aims to determine the efforts to build inclusive education that is oriented towards the independence of students through a responsive adaptive curriculum. The research method used is qualitative with a case study type. Data analysis used in this study uses the Milles and Huberman model analysis, namely data reduction, data presentation, and verification. The results of the study indicate that the strategy of Islamic boarding schools in realizing inclusive education that is oriented towards the independence of students in Islamic boarding schools utilizes a responsive adaptive curriculum whose main objective is to develop independence and inclusivity in the educational process at the Nurul Jadid Paiton Probolinggo Islamic boarding school as follows; development of an adaptive curriculum, adaptation to the needs of students, authentic assessment for independence.